α-Bisabolol alleviates diesel exhaust particle-induced lung injury and mitochondrial dysfunction by regulating inflammatory, oxidative stress, and apoptotic biomarkers through the c-Jun N-terminal kinase signaling pathway - Beegam, Sumaya; Zaaba, Nur Elena; Elzaki, Ozaz; Nemmar, Abderrahim (Frontiers in Pharmacology, 2025)
Particulate matter ≤ 2.5 μm in diameter (PM2.5) exposure is associated with adverse respiratory outcomes including alteration in lung morphology and function. These associations were reported even at concentrations lower than the current annual limit of PM2.5. Inhalation of PM2.5, of which diesel exhaust particles (DEP) is a major contributor, induces lung inflammation and oxidative stress. α-Bisabolol (BIS) is a bioactive dietary phytochemical with various pharmacological properties such as anti-inflammatory and antioxidant actions. Here, we evaluated the possible protective effect of BIS on DEP-induced lung injury. Mice were exposed to DEP (20 µg/mouse) or saline (control) by intratracheal (i.t.) instillation. BIS was given orally at 2 doses (25 and 50 mg/kg) 1h before DEP exposure. Twenty-four h after DEP administration, multiple respiratory endpoints were evaluated. BIS administration prevented DEP-induced airway hyperreactivity to methacholine, influx of macrophages, neutrophils and lymphocytes in the bronchoalveolar lavage fluid and the increase of epithelial and endothelial permeability. DEP exposure caused an increase in the levels of myeloperoxidase, proinflammatory cytokines and oxidative stress markers in the lung tissue homogenates, and all these effects were abated by BIS treatment. The activity of mitochondrial complexes I, II & III and IV were markedly increased in the lungs of mice exposed to DEP, and these effects were significantly reduced in BIS-treated group. I.t. instillation of DEP induced DNA damage and the increase in the apoptotic marker cleaved caspase-3. The latter effects were prevented in mice treated with BIS and exposed to DEP. Moreover, BIS mitigated, in a dose-dependent manner, DEP-induced increase in the expression of phospho-c-Jun N-terminal kinase (JNK). We conclude that BIS markedly alleviated DEP-induced lung injury by regulating inflammatory, oxidative stress and apoptotic biomarkers through the JNK signalling pathway. Awaiting additional studies, BIS may be considered as a plausible protecting agent against inhaled particle-induced pulmonary adverse effects.